2022
DOI: 10.21037/apm-21-3916
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of diagnostic test accuracy (DTA) studies: the role of cerebral perfusion imaging in prognosis evaluation of mild cognitive impairment

Abstract: Background: The application value of cerebral perfusion imaging, such as fluorodeoxyglucose-positronemission computed tomography (FDG-PET), single-photon emission computed tomography (SPECT), and structural magnetic resonance imaging (MRI), in the prognostic assessment of mild cognitive impairment (MCI) remains unclear. Thus, it was the focus of this meta-analysis, which aimed to provide a theoretical basis for early diagnosis of neurological diseases.Methods: The Boolean logic retrieval method was used to ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The levels of PPV/NPV were comparable with those of amyloid PET when considering these more advanced methodologies. A more recent metaanalysis was consistent with these results [36]. Of note, one study using voxel-based Cox regression as more advanced analysis approach found no advantage over established volume of interest-based analysis [37].…”
Section: Fdg-petmentioning
confidence: 57%
“…The levels of PPV/NPV were comparable with those of amyloid PET when considering these more advanced methodologies. A more recent metaanalysis was consistent with these results [36]. Of note, one study using voxel-based Cox regression as more advanced analysis approach found no advantage over established volume of interest-based analysis [37].…”
Section: Fdg-petmentioning
confidence: 57%
“…Molecular neuroimaging techniques [120,121] include dopaminergic single-photon emission computerized tomography (SPECT) [122][123][124][125][126][127][128][129], dopaminergic positron emission tomography (PET) [130][131][132][133], non-dopaminergic SPECT [134][135][136][137][138][139][140], non-dopaminergic PET [141-155,], and magnetic resonance spectroscopy (MRS) [156,157].…”
Section: Resultsmentioning
confidence: 99%
“…FDG-PET is a potential biomarker for the prodromal stage of DLB. Although FDG-PET imaging is superior for prognostic predictions of patients with MCI, cerebral perfusion imaging is also useful [23]. The CIScore for an AD group was signi cantly higher than that for DLB and MCI groups, as shown by an analysis performed using eZIS software (AD vs. DLB, p < 0.001; AD vs. MCI, p < 0.005) [24].…”
Section: Discussionmentioning
confidence: 98%